SOSIALISASI DAN PENDAMPINGAN PENYUSUNAN PEMBUKUAN SEDERHANA PRODUKSI INDUSTRI RUMAH TANGGA BERBASIS UBI KAYU DI DUSUN II KELURAHAN M. SITIHARJO - Febrina Nur Annisa; Syabawaihi Syabawaihi; Rio Rio; Ahmad Marsehan (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2023)
The objectives of this PKM activity are to (1) provide an understanding of the benefits of having bookkeeping in business administration, and (2) provide assistance to UMKM entrepreneurs who are the target group regarding procedures for compiling simple bookkeeping, especially in calculating the cost of production and profit and loss. The stages of implementation in PKM: the preparation stage, the training/socialization stage, the implementation stage, and the evaluation stage. This cassava-based processing business carried out by women in the M.Sitiharjo sub-district has adequate business prospects, and is possible to develop in the future. The implementation of this community service took place due to the open, adaptive and enthusiastic attitude of the participants. This situation, the existence of business potential for development, the expectations expressed by participants for this PKM activity to continue, as well as the existence of government policies to encourage the downstream of various products became the basis for consideration for the team to continue PKM activities in cassava-based home industry business groups that in the village of M. Sitiharjo.